Mild autonomous cortisol secretion portends similar cardiac compromise as overt endogenous Cushings syndrome. (4th February 2022) - Morbach, C; Hoffmann, K; Sahiti, F; Detomas, M; Eichner, F; Kroiss, M; Gelbrich, G; Frantz, S; Fassnacht, M; Heuschmann, PU; Hahner, S; Stoerk, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): German Ministry of Research and Education within the Comprehensive Heart Failure Centre Würzburg OnBehalf: CV-CortEx Background: Endogenous Cushing's syndrome (CS) results in increased cardiovascular morbidity and mortality. This risk seems to be lower in patients with incidentally discovered mild autonomous cortisol secretion (MACS) but without the clinical features of CS. We aimed to describe and compare the cardiac morphology and function in patients with overt CS and MACS to a representative sample of a local prospective population-based cohort (STAAB). Methods/Results: We comprehensively characterized 40 patients with overt CS (mean age 47 ± 13 years, 75% women) and 18 patients with MACS (62 ± 11 years, 56% women; both p ≤ 0.001 when compared to CS) including detailed transthoracic echocardiography. Logistic regression adjusted for age and sex showed no significant differences between both groups regarding body mass index (BMI), systolic and diastolic blood pressure (BP), lipids, HbA1c, and echocardiographic parameters of cardiac morphology and function (table). The comparison with STAAB participants (n = 4965, 55 ± 12 years, 52% women; logistic regression adjusted for age and sex) revealed significantly higher BMI, triglycerides, HbA1c, and diastolic but not systolic BP (table). Compared to STAAB participants, patients exhibited a smaller left ventricle (LV) with thicker septal and posterior walls, and a less favorable diastolic function. LV ejection fraction (LVEF) was higher, although longitudinal contraction, measured by tricuspid annular plane systolic excursion (TAPSE), and LV global longitudinal strain (GLS) were lower in both ventricles compared to STAAB participants (table). Conclusion: Patients with both MACS or CS exhibited a compromised metabolic profile and diastolic function pattern when compared to a population-based cohort. Higher LVEF despite lower GLS suggests a compensatory increase in LV radial contraction in states of hypercortisolism. Cardiac impairment was similar in patients with CS or MACS suggesting an adverse effect of hypercortisolism even at clinically inconspicuous levels.